Infection and colonization of pigeonpea genotypes with different degrees of susceptibility to wilt by Fusarium udum - T.N. RAJU, M.V. REDDY and (Indian Phytopathology, 2002)
The role of infection and colonization of 4 pigeon pea cultivars by F. udum was determined in Patancheru, Andhra Pradesh, India. Significant differences were recorded in Fusarium wilt incidence on the 4 cultivars at maturity but not at the seedling stage. At maturity, 7% wilt was recorded in the resistant cv. ICP 8863 compared with 83% in the susceptible variety ICP 2376. The results showed that although the cultivars differed in the extent of wilting, they did not differ in the extent of infectionor colonization.